IMPROVEMENT TOWERING CONTROL SYSTEM PADA TOWERLIGHT LS4-6000 DI PT.UNITED TRACTORS PANDU ENGINEERING - , YANTO WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The changes accur in the towering control system in Towerlight LS4-6000. Previously, a manual towering control system was used. Recently, it use hydraulic towering control system. In manual system for tilting and lifting used handle. As the result, some problems accur, they are he systemis less safety and is not practical. Therefore, the aim of this study is doing improvement by changing manual towering control system to hydraulic towering control system. The are some methods used in this study are. The first is collecting data information about hydraulic towering control system, the second is choosing compatible for tilting an lifting, the third is processing data which is obtained, the fourth is doing improvement on the towering, the fifth is doing test on the improvement. The result of improvement towering control system in Towerlight LS4-6000 unit shows that the best solution to finish the problem about unpracticability and unsafety in Towerlight LS4-6000 unit is using hydraulic system. It can make the hydraulic system more practical and safer. This safe improvement is used to avoid working accident and to shorten operation time. From the calculation, the number of pressure that is needed for tilting and lifting tower is 41.308 bar. The time needed to operate towerlight LS4-6000 is 17.56% faster.